Redes sociales y su influencia en las relaciones interpersonales de los estudiantes del colegio de bachillerato 27 de Febrero: desde un enfoque social - Gómez Cartuche, Oscar Alejandro (2024)
Social media has revolutionized how adolescents communicate and interact, yet it has also introduced a series of negative influences on their interpersonal relationships within the school environment. The pressure to maintain a flawless online image can lead to anxiety and low self- esteem, weakening relationships and group cohesion. These factors not only affect the emotional well-being of adolescents but can also create a hostile and divisive school atmosphere. This research analyzed the impact of social media on the interpersonal relationships of second-year high school students at the "27 de Febrero" school from a social perspective. It focused on characterizing social media usage, identifying the students' levels of interpersonal relationships, and determining the influence of social media use on these relationships. The study employed a mixed-methods approach, combining quantitative and qualitative data. It was exploratory and descriptive, allowing for a systematic examination of the issue. Additionally, it followed a deductive and descriptive approach to observe and analyze phenomena in their natural context. The sample consisted of 56 students distributed across three classes (B, D, and G), and techniques such as surveys and interviews were utilized. The findings indicate that social media negatively affects interpersonal relationships by often presenting idealized and filtered identities. Furthermore, its excessive use can lead to digital addiction, reducing the time devoted to studying and other important activities. Thus, it is crucial to implement educational programs that promote responsible and mindful use of social media among students.